Edukasi Pemanfaatan Tanaman Obat Keluarga (TOGA) di Pekarangan Taman Dasawisma RT 37 Perumahan Green View Regency Malang - Titik Wijayanti; Nurmala Hindun; Erfitra Rezqi Prasmala (Pusat Riset dan Inovasi Nasional, 2023)
This community service activity focuses on introducing education and the use of Family Medicinal Plants (FMP) in the garden of Taman Dasawisma RT 37 Green View Regency Malang. The implementation method for this program consists of five stages which include initial survey and preparation, training and education, FMP garden development, monitoring, and evaluation, as well as dissemination of results and sustainability. Through this activity, the community gains an in-depth understanding of FMP, selecting types of medicinal plants, processing, and utilization. This program has succeeded in making a significant positive contribution to the community. The direct impacts obtained include increasing knowledge about FMP, independence in health care, reducing health expenditure, developing a shared FMP garden, increasing environmental awareness, and improving quality of life. The success of this activity can become a role model for other communities to adopt a similar approach to improve the health and well-being of local communities.